2004
DOI: 10.1099/ijs.0.02907-0
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic characterization of nine strains isolated from clinical and environmental specimens, and proposal of Corynebacterium tuberculostearicum sp. nov.

Abstract: Nine unidentified Gram-positive, lipophilic corynebacteria were isolated from clinical and food samples and subjected to a polyphasic taxonomic analysis. The bacteria were distinguished from Corynebacterium species with validly published names by biochemical tests, fatty acid content and whole-cell protein analysis. Comparative 16S rRNA gene sequence analysis demonstrated unambiguously that the nine strains were related phylogenetically to the species ‘Corynebacterium tuberculostearicum’ and represented a dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 49 publications
0
21
0
2
Order By: Relevance
“…Furthermore, mRNA of all TLR genes including TLR 2 remained unaffected by exposure to S. e. (Figure 8A). At the protein level, immunocytochemistry and microscopic analysis confirmed that TLR 2 protein was increased 2.37-fold (P ≤ .001) after 24 Figure 8B, left panel). TNF mRNA expression was measured in HEKs cells treated for 2 hours with C. t. or FSL1 (Pam2CGDPKHPKSF), a synthetic lipopeptide and a specific TLR 2/6 agonist.…”
Section: T-induced Expression Of Inflammatory Genes In Heks and Smentioning
confidence: 82%
See 1 more Smart Citation
“…Furthermore, mRNA of all TLR genes including TLR 2 remained unaffected by exposure to S. e. (Figure 8A). At the protein level, immunocytochemistry and microscopic analysis confirmed that TLR 2 protein was increased 2.37-fold (P ≤ .001) after 24 Figure 8B, left panel). TNF mRNA expression was measured in HEKs cells treated for 2 hours with C. t. or FSL1 (Pam2CGDPKHPKSF), a synthetic lipopeptide and a specific TLR 2/6 agonist.…”
Section: T-induced Expression Of Inflammatory Genes In Heks and Smentioning
confidence: 82%
“…), 21 while other species, such as toxigenic C. diphtheriae, are classified as serious and potentially life-threatening pathogens. 22,23 The species C. tuberculostearicum (C. t.), characterized by C. Feurer et al in 2004 24 is a major component of the bacterial species that colonize a variety of skin environments, including dry, moist, and sebaceous regions. 25 Several studies have associated C. t. with disease states, including inflammatory breast disease, pancreatic panniculitis, chronic rhinosinusitis, and surgical site infections.…”
Section: Introductionmentioning
confidence: 99%
“…L. clevelandensis was only first described in 2013 (Harrington et al, 2013) and has since been repeatedly associated with abscess formation (Bell et al, 2016;Menezes et al, 2018); however, very recent research suggests it is a common human (nasal) commensal (Escapa et al, 2018). C. tuberculostearicum has traditionally been termed a 'leprosy-derived' Corynebacterium, having been first isolated from a Lepromatous leprosy case (Brown et al, 1984;Feurer et al, 2004); the OTU sequence here was a unique 100% identity match with this (type) strain Medalle X. Recent research, isolating 18 C. tuberculostearicum strains from human clinical specimens (Hini c et al, 2012), demonstrated multiple antimicrobial resistance in most isolates (but importantly, 100% susceptibility to vancomycin) and classified 7 of the 18 isolates as being clinically relevant to surgical site infection [centers for disease control (CDC) criteria (Henriksen et al, 2010)].…”
Section: Real-world Data Testing: International Space Station Data Setmentioning
confidence: 99%
“…Bacteria of the genus Corynebacterium have been recovered extensively from mammals and the environment (Feurer et al, 2004;Hommez et al, 1999). Except for Corynebacterium diphtheriae, the aetiological agent of diphtheria, most species of the genus are regarded as opportunistic pathogens (Paviour et al, 2002).…”
mentioning
confidence: 99%